Situated Agency in Digitally Artifacted Social Interactions: Introduction to the Special Issue - Ibnelkaïd, Samira; Avgustis, Iuliia (Social Interaction. Video-Based Studies of Human Sociality, 2023)
This special issue brings together video-based studies on the local accomplishment of human and non-human agency in digitally artifacted social interactions. It seeks to overcome the dual ontological approach to agency by observing its situated, multimodal, and dynamic enactment by interactants. This gathered body of research explores the notion of situated agency through various lenses. Contributions to this issue can be split into four groups: human-chatbot interactions (smart speakers and service telephone chatbots), human-robot interactions (social robots and robots in educational settings), interactions with digital technologies in specific contexts (autonomous cars and pedestrians, virtual reality and atypical users), and face-to-face human interactions involving the use of digital devices in mundane settings.